Student Inquiry, Networks of Knowledge and Linked Data - Carmichael, Patrick; Tracy, Frances (Proceedings of the International Conference on Networked Learning, 2018)
This paper explores the potential for the development of new learning opportunities in higher education, through students being conceptualised not as consumers, recipients or commodities, but rather as co-researchers and co-producers of knowledge. Specifically, it discusses the implications of new forms of networked knowledge enabled by the emergence of semantic web and linked data technologies and the reconceptualising of the Internet as a ‘global data space’. We draw on our experience of initiating and supporting a range of projects in UK higher education in the course of an extended programme of research and development. Some of these involved the design and development of new technology platforms, while others were focussed on the redevelopment of taught courses, assignments and assessed activities. What these projects had in common is that they all took place in the context of complex learning settings in which some variety of case based learning is used. They involved students drawn from different disciplines in higher education in ‘research-based learning’ about curriculum contexts, and about pedagogical aspects of these contexts. New digital tools were developed in the form of rich web applications that allowed learner interaction with content, in many cases underpinned by data from multiple sources and in diverse formats. In the development of these online technologies, students located, analysed, synthesised and, in some cases, generated new data, and, perhaps more significantly, participated in local or global knowledge networks. What we will argue is that these types of projects involve not only the development of specific techno-literacies, but also that they form the basis of broader ‘critical digital literacies’. These in turn equip students to enter workplaces better positioned to inquire into the particularities of the educational settings in which they work and the practices in which they are engaged. They can thus undertake ‘counter-research’ in which dominant rhetorics are challenged, and evidence bases for policy and practice are subjected to scrutiny, critique and reinterpretation. This presents the potential for students to undertake critical and politicised inquiry as part of a broader reframing of the purposes of higher education.